Surface properties, adhesion and biofilm formation on different surfaces by Scedosporium spp. and Lomentospora prolificans. Issue 7 (9th August 2018) - Mello, Thaís P.; Oliveira, Simone S. C.; Frasés, Susana; Branquinha, Marta H.; Santos, André L. S.
Abstract: In the present work, some surface properties of the fungi Scedosporium apiospermum, S. aurantiacum, S. minutisporum, and Lomentospora prolificans and their capability to adhere to and form a biofilm on diverse surfaces were evaluated. All four species had high conidial surface hydrophobicity and elevated electronegative zeta potentials. Abundant quantities of melanin were detected at the conidial surface, whereas sialic acid was absent. The numbers of non-germinated and germinated conidia adhered to poly-L-lysine-covered slides was higher than on glass after 4 h of fungi–surface contact. Additionally, after 72 h of interaction a typical biofilm structure had formed. Mature biofilms were also observed after 72 h on a nasogastric catheter (made from polyvinyl chloride), a late bladder catheter (siliconized latex), and a nasoenteric catheter (polyurethane). Interestingly, biofilm biomass increased considerably when the catheters had previously been incubated with serum. These results confirm that Scedosporium/Lomentospora spp. are capable of forming biofilms on diverse abiotic surfaces.